Boca do Inferno: Adaptação cinematográfica da novela policial que Fernando Pessoa não escreveu - Miraglia, Gianluca (Pessoa Plural)
The film Boca do Inferno by Luís Porto has the particularity of being inspired by a detective novel, The Mouth of Hell, which Fernando Pessoa attempted to write after staging the suicide of Aleister Crowley, the occultist’s final act during his stay in Portugal. Analyzing the relationship between the film’s plot and the detective fiction allows for a deeper understanding of this Pessoa text, which was only revealed in the early 21st century.